Evaluation of factors affecting microbial growth inhibition and optimization using pineapple leaves juice - Norazwina, Zainol; Amirah, Ya’acob; Putri Nurul Yasmin, Mohd Ridza; Siti Hatijah, Mortan; Kamaliah, Abdul Samad (Universiti Putra Malaysia Press, 2022)
This study optimized microbial growth inhibition conditions using pineapple leaf juice (PLJ). The sugarcane press machine was used to press the PLJ. The study considered four factors to be analyzed by Two-level factorial design (TLFD), which are microbial inhibition time (0.5–5 h), the concentration of total phenolic content (TPC) (0.2563–0.5127 mg GAE/ mL), temperature (26–37 °C), and the ratio of PLJ to microbe (PLJ/M) (v/v) (1:1 and 1:3). Colony-forming unit (CFU) method was employed to measure microbial growth inhibition. The microbial growth inhibition was expressed as a percent in terms of CFU/mL. A central composite design (CCD) experimental design created using response surface methodology (RSM) determined the optimum temperature (35–39 °C) and microbial inhibition time (10–50 min) of microbial growth inhibition. The best conditions were 0.5 h of microbial inhibition time, 0.5127 mg GAE/mL of TPC, 1:1 PLJ/M, and a temperature of 37 °C. The analysis of variance (ANOVA) showed that temperature (Factor C) has the greatest contribution (1.56%) to inhibiting microbial growth, accompanied by TPC concentration in PLJ (Factor B) with 1.27%, microbial inhibition time (Factor A) with 1.07% and PLJ/M (Factor D) 0.29%. Optimization studies show that at an optimum temperature of 37 °C and an inhibition time of 34.25 min, maximum microbial growth inhibition of 94.73% with a minimum value of 9.12×104 CFU/mL was achieved. This research suggests that PLJ can be utilized as a value-added natural product for application in the agricultural sector.